Structural variation and diadochokinetic sequencing in the cerebral plasied and normals - Renuka Mahadevan (Journal of All India Institute of Speech and Hearing, 1970)
The present study was aimed at finding out the possible relationships between the different oral structures and the diadochokinetic tasks in thenormals and the cerebral palsied population. The study also aimed at comparing the performance of different age groups in normals and C.P. subjects on the isolated, combined and isolated Vs combined diadochokinetic tasks, cognate pair comparison on the different DDK tasks and to see if a developmental trend exists in the normal and C.P. population.